Theophilus and the theory and practice of medieval art - Gearhart, Heidi C., 1976- (The Pennsylvania State University Press, 2017)
"Explores Theophilus' On Diverse Arts, a twelfth-century treatise on artistic techniques. Examines the system of values according to which medieval artists operated and created art objects"--Provided by publisher